Choice not chance : - McCallie, Joanne (Wiley, 2012)
Throughout her pioneering career in college basketball, Coach Joanne P. McCallie has followed a simple philosophy: Choice, not chance, determines destiny. Choose to become a champion in life. From her first head coaching position at age 26 to her current role as head coach for the Duke Blue Devils, McCallie has enjoyed sharing these principles with her winning teams and the youth in the communities where she and her family have lived.